CD4+ T‐cell depletion in HIV infection: mechanisms of immunological failure. Issue 1 (16th June 2013) - Okoye, Afam A.; Picker, Louis J.
Summary: The hallmark of acquired immunodeficiency syndrome (AIDS) pathogenesis is a progressive depletion of CD4 + T‐cell populations in close association with progressive impairment of cellular immunity and increasing susceptibility to opportunistic infections (OI). Disease progression in untreated human immunodeficiency virus (HIV) infection can take many years, and it was originally hypothesized to be a consequence of slow, viral‐mediated CD4 + T‐cell destruction. However, massive CD4 + memory T‐cell destruction is now known to occur quite early in infection, almost always without overt immunodeficiency. In most individuals, this initial destruction is countered by CD4 + memory T‐cell regeneration that preserves CD4 + T‐cell numbers and functions above the threshold associated with overt immunodeficiency. This regeneration, which occurs in the setting of chronic immune activation and immune dysregulation does not, however, restore all functionally important CD4 + T‐cell populations and is not stable over the long term. Ultimately, CD4 + memory T‐cell homeostasis fails and critical effector populations decline below the level necessary to prevent OI. Thus, the onset of overt immune deficiency appears to be intimately linked with CD4 + memory T‐cell dynamics and reflects the complex interplay of direct viral cytopathogenicity and the indirect effects of persistent immune activation on CD4 + memory T‐cell proliferation, differentiation, and survival.